Influence of climate change on tri-trophic interaction in maize (Zea mays) ecosystem - LALBIAKZUALI; SREENIVAS, A G (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2022–23 at University of Agricultural Sciences, Raichur, Karnataka to investigate the influence of climate change in maize (Zea mays L.) ecosystems against maize fall armyworm, Spodoptera frugiperda; and with a focus on parasitoids, Trichogramma chilonis (egg parasitoid) and Goniozus nephantidis (larval parasitoid). The study was done under Open Top Chambers (OTCs) with treatments T1, Ambient CO2 at 410 ppm with 31ºC (Reference OTC); T2, Ambient CO₂ at 410 ppm with a 2ºC rise in temperature; T3, Elevated CO2 at 550 ppm with 31ºC; T4, Elevated CO2 at 550 ppm with a 2ºC rise in temperature and T5, Reference (open) field. The results revealed that under elevated CO2 at 550 ppm + raised temperature at 33⁰C, the plant height, number of leaves, and chlorophyll content increased along with grain and fodder yield. However, decreased in foliar nitrogen levels of maize leaves forced fall armyworm to eat more plant material to acquire the nutrition required, causing greater crop damage. This led to more larval weight (592.0 ± 1.64 mg) and prolonged larval duration (28.03 ± 0.05 days), while decreasing pupal weight (225.7 ± 6.37 mg), female fecundity (720/female) indicating reduced overall fitness. At the tri-trophic level, both the parasitoids showed reduced performance under climate change conditions. T. chilonis had lower success rates in attacking pest eggs (63.16% parasitism, 61.93% emergence) and took longer to develop (11 days). Similarly, G. nephantidis produced smaller adults (3.50 mm ± 0.02 mm) with reduced emergence rates (66.07%) due to the compromised quality of their hosts as a result of climate change. This research demonstrates how climate change disrupts natural pest control systems, potentially making crop protection more challenging in the future.